Clinical characteristics and predictive models of HER2-low breast cancer patients who only received adjuvant chemotherapy: a real-world retrospective multicenter study - Qinchuan Wang; Yuying Wang; Zikang Chen; Yuqing Chao; Lin Chen; Wenjing Li; Xia Yang; Zhinong Jiang; Xiaoyan Li; Bo Gao; Wenxian Hu; Jichun Zhou; et al. (npj Precision Oncology)
Abstract HER2-low positivity is reported to play substantial role in neoadjuvant chemotherapy for breast cancer, but its role in adjuvant chemotherapy remains unclear. We aim to explore the role of HER2-low positivity in the breast cancer patients who only received adjuvant chemotherapy. We evaluated 3214 patients from SRRSH Hospital and 16,273 patients from CHLP Hospital. All the patients were diagnosed as primary breast cancer who only received adjuvant chemotherapy. HER2-status was defined according to ASCO/CAP guidelines. Multivariable Cox models and machine learning models were applied in the analysis of overall survival. A total of 1009 HER2-zero, 1399 HER2-low and 806 HER2-positive patients were included in SRRSH cohort, while there were 5662 HER2-zero, 6471 HER2-low and 4140 HER2-positive patients in CHLP cohort. HER2-low patients showed significant better OS and reduced death risk compare to HER2-zero patients in both SRRSH (log-rank p = 0.033, HR = 0.62, 95% CI 0.39–0.97, p = 0.037) and CHLP cohort (log-rank p < 0.001, HR = 0.63, 95% CI 0.55–0.73, p < 0.001). In subgroup analysis, HER2-low patients had significantly reduced risk of death compare to HER2-zero patients in hormonal receptor-positive subset in both cohorts, but not in hormonal receptor-negative subset. MLP model demonstrated the best performance among all the predictive models in both cohorts. Our study indicated that HER2-low patients had better survival compare to HER2-zero patients in adjuvant chemotherapy only setting. We emphasized the significance of HER2 status in adjuvant setting in BC, implying more precise diagnostic and therapeutic strategies in future.